A corporate-centred conservative welfare regime: three-layered protection in Japan. Issue 1 (2nd January 2021) - Shizume, Masato; Kato, Masatoshi; Matsuda, Ryozo
ABSTRACT: The Japanese welfare model is identified by the unified typology method of welfare and production regime (Schröder 2013 ) as the corporate-centred conservative welfare regime (CCWR), a subgroup of the conservative welfare regime. The major company cross-class alliance (Ito, 1988 ) has played a pivotal role in constructing the CCWR under the group-based coordinate market economy (Hall & Soskice, 2001, 2007 ). It encompasses the following key characteristics: a male breadwinner-based social insurance with status-dependent programs and a greater role of occupational welfare. Therefore, it fragments social protection into a three-layered structure where regular employees of major enterprises, especially men, enjoy the most generous benefits from their company and government, followed by permanent labourers of small- to medium-sized firms who are provided for relatively modestly, while only minimum governmental benefit is allocated to non-regular employees.